Brain-Derived Neurotrophic Factor: A Connecting Link Between Nutrition, Lifestyle, and Alzheimer’s Disease - Xue, Bin; Waseem, Shah Mohammad Abbas; Zhu, Zhixin; Alshahrani, Mohammed A.; Nazam, Nazia; Anjum, Farah; Habib, Alaa Hamed; Rafeeq, Misbahuddin M.; Nazam, Fauzia; Sharma, Monika (Frontiers in Neuroscience, 2022)
Brain-derived neurotrophic factor (BDNF) involving tropomyosin kinase B and low affinity p75 neurotropin receptors is the most abundant and researched neurotropins in mammal’s brain. It is one of the potential targets for therapeutics in Alzheimer’s disease (AD) owing to its key role in synaptic plasticity. Low levels of BDNF are implicated in the pathophysiology of neurological diseases including AD. However, a healthy lifestyle, exercise, and dietary modifications are shown to positively influence insulin regulation in the brain, reduce inflammation, and up-regulate the levels of BDNF, and are thus expected to have roles in AD. In this review, the relationship between BDNF, mental health, and AD is discussed. Insights into the interrelationships between nutrition, lifestyle, and environment with BDNF and possible roles in AD are also provided in the review. The review sheds light on the possible new therapeutic targets in neurodegerative diseases.